Estimating the Optimal Stochastic Dominance Efficient Set with a Mean-Semivariance Algorithm - Bey, Roger P. (Journal of Financial and Quantitative Analysis, 1979)
Roger P. Bey, Estimating the Optimal Stochastic Dominance Efficient Set with a Mean-Semivariance Algorithm, The Journal of Financial and Quantitative Analysis, Vol. 14, No. 5 (Dec., 1979), pp. 1059-1070